Innovation in banana value chain development in Metema District, Northwestern Ethiopia: Improving Productivity and Market Success (IPMS) project experiences - Berhe, Kahsay; Puskur, Ranjitha; Teka, W.; Hoekstra, Dirk; Tegegne, Azage (International Society for Horticultural Science, 2010)
Ethiopia has a diverse agro-ecology suitable for growing various temperate and tropical fruits. However, the area under fruits is very limited. The limited development of the fruit sector in the country could be attributed to input supply constraints, limited skilled manpower and extension approaches, and focus of agricultural development efforts on grain production, amongst others. The current government’s policy and development strategy prioritize intensive production and commercialization of agriculture, including fruit production. In an effort to support this change, the International Livestock Research Institute (ILRI) and the Ministry of Agriculture and Rural Development (MoARD) initiated a 5-year project with financial assistance from Canada, called Improving Productivity and Market Success (IPMS) of Ethiopian farmers. IPMS follows participatory value chain and innovation system perspectives and focuses on knowledge-based development of identified agricultural commodities with market potential in ten pilot learning ‘weredas’ (districts) in four regional states. One of the ‘weredas’ is Metema, where the project introduced banana (Musa spp.) production. The objective of this study is to share IPMS experiences in promoting innovation in banana value chain development in Metema ‘wereda’. The study provides a brief history of banana introduction in Ethiopia, describes the value chain in banana production, and input supply, marketing and the various innovations that have been introduced to develop the chain, with a focus on actors and action-learning processes. We highlight the future outlooks on the banana value chain, the reasons for successful adoption of innovations and the options to sustain it so that the value chain can respond to changing conditions.